1980 19th IEEE Conference on Decision and Control Including the Symposium on Adaptive Processes 1980
DOI: 10.1109/cdc.1980.271924
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic positioning of floating vessles based on Kalman filtering and optimal control

Abstract: This paper describes a computer-based, dynamic positioning system for floating vessels. The system is based on a detailed mathematical model of vessel motioninresponse to forces from thrusters, wind, waves and water current. The system uses a Kalman filter for optimal estimation of vessel motions and enviromental forces from wind, waves and current. The control where the oscillatory, wave-induced component is system is based on feedback from the motion variables removed by the estimator. Feedback from the wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 1 publication
0
29
0
1
Order By: Relevance
“…These filters are used to provide estimates of the vessel velocities since the vessel's velocities are usually not measured in a dynamic positioning system. See for example Balchen et al (1980), Grimble et al (1980), Sorensen et al (1996).…”
Section: Introductionmentioning
confidence: 98%
“…These filters are used to provide estimates of the vessel velocities since the vessel's velocities are usually not measured in a dynamic positioning system. See for example Balchen et al (1980), Grimble et al (1980), Sorensen et al (1996).…”
Section: Introductionmentioning
confidence: 98%
“…The LQG design technique was first applied to dynamic positioning by ( [3], [4]) and ( [5], [6]). Later Grimble and co-authors suggested both H and μ-methods for filtering and control ( [7], [8]).…”
Section: Introductionmentioning
confidence: 99%
“…The current research on PM systems is based on the experience obtained from research on dynamic positioning (DP) systems since the 1970's. DP systems based on optimal control theory and Kalman-filtering were proposed in [1], and extended in [2], [3], [4], [5], [6], [7] and [8]. In recent years, nonlinear controllers have been developed for DP systems based on integrator backstepping techniques (see [9], [10], [11] and [12]).…”
Section: Introductionmentioning
confidence: 99%